High‐Detectivity Green‐Selective All‐Polymer p–n Junction Photodetectors. Issue 23 (19th October 2020) - Kang, Jinhyeon; Kim, Junho; Ham, Hyobin; Ahn, Hyungju; Lim, Soo Yeong; Kim, Hyung Min; Kang, In‐Nam; Jung, In Hwan
Abstract: Currently available wavelength‐selective p–n junction organic photodetectors (OPDs) nearly exclusively use small molecules. In this study, green (G) selective all‐polymer p–n junction OPDs are developed by engineering the π‐conjugation networks and insulating properties of p‐ and n‐type polymers. Enhanced intermolecular ordering of p–n junction blend films compared to pristine polymer films results in superior hole/electron mobilities and low bimolecular recombination in the devices. Notably, similar G absorption ranges and the huge difference in their absorption coefficients between p‐ and n‐type polymers make excellent G selectivity in the p–n junction OPDs. Thus, narrow selectivity with a full width at half maximum of 155 nm toward green light and high detectivity of ≈10 13 Jones are achieved in the all‐polymer p–n junction OPDs. Abstract : Green selective p–n junction all‐polymer photodetectors are developed by designing p‐ and n‐type conjugated polymers. Narrow selectivity with a full width at half maximum of 155 nm toward green light, high detectivity of ≈10 13 Jones, and fast signal responses are achieved.